Enhancing hydroponic vegetable productivity using environmentally friendly cow biourine fertilizer technology as nutrient solution - Akbar Choer; Rosadi Rosadi; Sri Wahyuni (Indonesian Journal of Applied Environmental Studies, 2025)
The increasing scarcity of arable land and agricultural inputs has encouraged the adoption of innovative cultivation systems such as hydroponics, with vegetables being among the most suitable commodities. Hydroponic cultivation commonly relies on AB Mix as the primary nutrient source; however, the availability of livestock resources, particularly cow urine, presents an opportunity to develop biourine as an environmentally friendly alternative to synthetic fertilizers. This study employed a quantitative experimental approach using a Complete Randomized Factorial Design to examine the effects of different combinations of AB Mix and cow biourine on the growth and productivity of hydroponic vegetables. Treatments consisted of varying concentration ratios of AB Mix and biourine, with evaluation focused on vegetative parameters including plant height, leaf length, leaf width, number of leaves, and post-harvest yield. Results demonstrated that spinach (Amaranthus sp.) and water spinach (Ipomoea aquatica) exhibited optimal growth under treatments dominated by AB Mix, particularly at the P4 ratio (75% AB Mix + 25% biourine), which significantly improved vegetative growth and yield compared to other treatments. Conversely, bok choy (Brassica rapa var. chinensis) responded more favorably to biourine-dominated treatments, with the P5 ratio (25% AB Mix + 75% biourine) producing the best performance across measured parameters. These findings indicate that biourine can partially substitute for AB Mix in hydroponic systems, with crop-specific responses determining the optimal formulation. The study highlights the potential of livestock-derived biourine as an eco-friendly fertilizer alternative, reducing reliance on synthetic inputs and supporting sustainable hydroponic vegetable production.